FAKTOR DETERMINASI NILAI PERUSAHAAN DI SEKTOR OTOMOTIF DAN KOMPONENNYA - Berliana, Chantika; Yovita, Lenni (LPPM Universitas Bina Bangsa, 2025)
This research aims to examine the influence of financial performance and stock price on company value. Financial performance indicators consist of profitability and liquidity. In this research, a quantitative method was applied. Data collection was carried out by utilizing secondary data sourced from financial statements and company stock price data. This study analyzed 12 firms operating in automotive and components listed at Indonesia Stock Exchange (IDX), focusing on the seven year timeframe from 2017 to 2023. Samples were selected by applying purposive sampling technique to carefully select companies. This research uses multiple linear regression technique and utilizing IBM SPSS Statistics software. The result showed that the profitability (ROA) having a positive but non-significant influence on firm value (PBV). Liquidity (CR) and stock price have a positive and significant influence on firm value (PBV). From the research findings, it can be concluded that although profitability is an important aspect in the company, investors tend to consider other aspects such as liquidity and stock price when determining the company’s value.